Dynamics of Transformation of the Rural Workforce Structure in West Bengal, 1961-2001. - Ghosal, Ratan Kumar (2006)
This paper examines the dynamics of the nature of transformation of rural workforce structure in West Bengal on the basis of NSSO and Census data. It finds that the workforce participation rates in the state are relatively lower as compared to the same at the national level. However, the proportions of rural workforce employed in different industrial categories of non-farm activities have been found to be muchhigher in the State than the national level. Over time the fall in employment in farming activities has been compensated by the rise in employment in manufacturing and household industries and other categories of non-farm activities like trade, hotelling, construction, storage, transport etc. In fact the state and its districts have experienced a tremendous increase in the rural non-farm employment along with an increasing tendency of feminization of rural employment structure especially during the period of reform. It seems that the process of diversification of rural workforce in the state may partly be agricultural growth led and partly distress driven.